Exploration of the Direct Use of Anodized Alumina as a Mold for Nanoimprint Lithography to Fabricate Magnetic Nanostructure over Large Area - M. Tofizur Rahman; Hao Wang; Jian-Ping Wang (Journal of Nanotechnology)
We have explored the direct use of anodized alumina (AAO) fabricated on an Si wafer as a mold for the nanoimprint lithography (NIL). The AAO mold has been fabricated over more than 10 cm2 area with two different pore diameters of 163±24 nm and 73±7 nm. One of the key challenges of the lack of bonding between the antisticking self-assembled monolayer (SAM) and the AAO has been overcome by modifying the surface chemistry of the fabricated AAO mold by coating it with thin SiO2 layer. Then we have applied the commonly used silane-based self-assembled monolayer (SAM) on these SiO2-coated AAO molds and achieved successful imprinting of resist pillars with feature size of 172±25 nm by using the mold with a pore diameter of 163±24 nm. Finally, we have achieved (001) oriented L10 FePt patterned structure with a dot diameter of 42±4 nm by using a AAO mold with a pore diameter of 73±7 nm. The perpendicular Hc of the unpatterned and patterned FePt is about 3.3 kOe and 12 kOe, respectively. These results indicate that AAO mold can potentially be used in NIL for fabricating patterned nanostructures over large area.